1999
DOI: 10.1177/026119299902700506
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hepatocyte Cultures and Liver Slices in In Vitro Toxicity Testing

Abstract: The aim of this study was to compare the in vitro toxicities of two hepatotoxins in hepatocyte cultures and in liver slices from both rats and dogs. Hepatocytes and liver slices were pre-incubated for 2 hours and then exposed to galactosamine or paracetamol, both of which mainly induce liver necrosis in vivo. Following exposure to the compounds for 20 hours, neutral red uptake (NRU [hepatocyte cultures only]), MTT reduction, and reduced glutathione (GSH), adenosine triphosphate (ATP) and protein content, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Recently, precision-cut liver slices have been utilized as an alternative method since the approach maintains tissue architecture and functional heterogeneity and provides a pathway for drug metabolism that is more consistent with in vivo metabolism than other models (Smith et al 1987, Barr et al 1991, Dogterom 1993, Miller et al 1993, Saylers et al 1994, George et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, precision-cut liver slices have been utilized as an alternative method since the approach maintains tissue architecture and functional heterogeneity and provides a pathway for drug metabolism that is more consistent with in vivo metabolism than other models (Smith et al 1987, Barr et al 1991, Dogterom 1993, Miller et al 1993, Saylers et al 1994, George et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in agreement with previous studies. For instance, it had been demonstrated that 24 h after the exposure of isolated hepatocytes to APAP, a more rapid decrease in the levels of ATP and GSH occurred, indicating a larger decrease in hepatocyte viability [ 77 ]. By contrast, it is assumed that, where the tissue structure is maintained (in the slices and ex vivo samples), when the action of APAP is stopped, the mechanisms of ATP resynthesis are activated, this also explaining their increase in the contribution of the bound form of NAD(P)H [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The exposure of slices to ethanol for 24 h is not enough to allow for the analysis of the metabolic changes that had been clearly observed in the slices in the APAP hepatotoxicity model. This is probably associated with the resistivity of the hepatocytes to the toxic effects of ethanol in the slice model due to the preservation of the native tissue structure [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%